2019
DOI: 10.3758/s13421-018-0890-9
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the perceptual-conceptual barrier: Relational matching and working memory

Abstract: Cognitive, comparative, and developmental psychologists have long been interested in humans' and animals' ability to respond to abstract relations, as this ability may underlie important capacities like analogical reasoning. Cross-species research has used relational matching-to-sample (RMTS) tasks in which participants try to find stimulus pairs that Bmatch^because they both express the same abstract relation (same or different). Researchers seek to understand the cognitive processes that underlie successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…First, the working memory demands required to hold on to choices while awaiting deferred feedback probably interferes more with the discovery of abstract relational concepts like same/different than with the discovery of basic perceptual concepts like square/rectangle. This would be consistent with recent research showing that concurrent working memory load interferes with participants’ transition from perceptually based matching to conceptual same/different matching in a relational match to sample task (Smith et al, 2019). Second, in E2, hypothesis testing had to operate over a deferral of 6 trials in a block, not just 1 lagged trial as in E1.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…First, the working memory demands required to hold on to choices while awaiting deferred feedback probably interferes more with the discovery of abstract relational concepts like same/different than with the discovery of basic perceptual concepts like square/rectangle. This would be consistent with recent research showing that concurrent working memory load interferes with participants’ transition from perceptually based matching to conceptual same/different matching in a relational match to sample task (Smith et al, 2019). Second, in E2, hypothesis testing had to operate over a deferral of 6 trials in a block, not just 1 lagged trial as in E1.…”
Section: Resultssupporting
confidence: 92%
“…A second learning process resident in working consciousness can explain this shift. In fact, Smith et al (2019) showed they could disrupt this learning process using working memory interference in a relational task like that used in Experiment 2. Third, a single system cannot explain the transition from concrete-perceptual to abstract-conceptual information.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, we began investigating the perceptual factors that influence pigeons’ two-item same–different performance—an area that past research had not yet addressed (cf., Wright & Sands, 1981; who explored how pigeons’ matching-to-sample decisions were impacted when both response options were of varying distances from the sample, as well as Smith et al, 2019; who assessed how varying distances from a prototype influenced humans’ responding in relational matching-to-sample). Specifically, we asked how pigeons’ responding might depend on the perceptual disparity between the members of each different-item pair.…”
Section: Discussionmentioning
confidence: 99%